Saphenous Nerve Somatosensory-Evoked Potentials Monitoring During Lateral Interbody Fusion. Issue 5 (June 2021) - Jain, Nick; Alluri, Ram; Phan, Kevin; Yanni, Daniel; Alvarez, Andrew; Guillen, Herbierto; Mnatsakanyan, Lilit; Bederman, S. Samuel
Study Design: Retrospective cohort study. Objectives: To clinically evaluate saphenous nerve somatosensory-evoked potentials (SSEPs) as a reliable and predictable way to detect upper lumbar plexus injury intraoperatively during lateral lumbar trans-psoas interbody fusion (LLIF). Methods: Saphenous nerve SSEPs were obtained by stimulation of inferior medial thigh with needle electrodes and recording from transcranial potentials. The primary outcome was measured by testing reproducibility of SSEPs at baseline, changes during the procedure, and relevance to standard modalities. Significant SSEP changes were compared with actual postoperative nerve complications. The sensitivity and specificity of saphenous SSEPs to detect postoperative lumbar plexus nerve injury was calculated. Results: A total of 62 patients were included in the study. Reliable saphenous SSEPs were recorded on the LLIF approach side in 52/62 patients. Persistent saphenous SSEP reduction of amplitude of >50% in 6 cases was observed during expansion of the tubular retractor or during the procedure. Two of 6 patients postoperatively had femoral nerve sensory deficits, and 5 of 6 patients had mild femoral nerve motor weakness, all of which resolved at an average of 12 weeks postoperatively (range 2-24 weeks). One patient had saphenous SSEP changes but demonstrated intraoperative recovery and had no postoperative clinical deficits. Saphenous SSEPs demonstrated 52% to 100% sensitivity and 90% to 100% specificity for detecting postoperative femoral nerve complications. Conclusion: Saphenous SSEPs can be used to detect electrophysiological changes to prevent femoral nerve injury during LLIF. Intraoperative SSEP recovery after amplitude reduction or loss may be a prognostic factor for final clinical outcome.